Role of probiotics to control gut-related diseases in animals - U. Laila; T. Varkey; M. Akram; M. Iftikhar; R. Zainab; T. Khalil; S. Adonis; G. Sołowski; F. Ahmet Ozdemir; M. Altable; C. Zeitler; Z. Merhavy (Microbiota in Health and Disease)
The role of probiotics is significant for both human and animal health and is also involved in several functional applications and the creation of animal foods. The various types of research showed that the potential of probiotics is significant in several fields. However, a growing research interest in their application and benefits in ruminant production has been established. For the development of livestock breeding, different procedures are used, and the expectation of breeders is that probiotics show promising effects, including enhancing the growth rate of livestock, showing protective effects against various pathogens, and increasing production. Their application helps to achieve beneficial effects that are comparable to those of antibiotic-based growth stimulators banned on January 1st, 2006. Thus, the livestock expects that the use of probiotics, prebiotics, and symbiotics will enable better maintenance of the equilibrium of the intestinal microbiota of livestock to prevent disease in both their animals and the end consumer.